2017
DOI: 10.1016/j.neuroscience.2017.08.013
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent binge ethanol exposure alters specific forebrain cholinergic cell populations and leads to selective functional deficits in the prefrontal cortex

Abstract: Adolescence has been identified as a vulnerable developmental time period during which exposure to drugs can have long-lasting, detrimental effects. Although adolescent binge-like ethanol (EtOH) exposure leads to a significant reduction of forebrain cholinergic neurons, EtOH’s functional effect on acetylcholine (ACh) release during behavior has yet to be examined. Using an adolescent intermittent ethanol exposure model (AIE), rats were exposed to binge-like levels of EtOH from postnatal day (PD) 25–55. Three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 105 publications
(154 reference statements)
4
90
0
Order By: Relevance
“…Historically, AIE has been shown to reduce populations of ChAT+IR neurons in the basal forebrain of adult male rodents [ 16 18 , 57 ], but to date no studies have assessed the effect of AIE on ChAT expression in the basal forebrain of adult females. In the present study, we found that expression of ChAT in control male and female Wistar rats did not differ as a function of sex, which is consistent with data reporting similar numbers of basal forebrain ChAT+IR neurons in aging male and female rats (i.e., 12 mo—25 mo; [ 58 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, AIE has been shown to reduce populations of ChAT+IR neurons in the basal forebrain of adult male rodents [ 16 18 , 57 ], but to date no studies have assessed the effect of AIE on ChAT expression in the basal forebrain of adult females. In the present study, we found that expression of ChAT in control male and female Wistar rats did not differ as a function of sex, which is consistent with data reporting similar numbers of basal forebrain ChAT+IR neurons in aging male and female rats (i.e., 12 mo—25 mo; [ 58 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intake of alcohol is linked, other than to cardiac and liver problems, to cognitive impairments and brain damage. The characteristics of dementia due to excessive alcohol drinking have received increased interest, and both neuropathological and imaging studies have suggested that excessive and prolonged use of alcohol may be responsible for structural and functional brain damage [70][71][72]. Chronic or excessive alcohol consumption may cause damage to the temporal lobe similar to that observed in AD [73].…”
Section: High Wine Consumptionmentioning
confidence: 99%
“…Rats were returned to standard pair-housing conditions after VEx/Stat for 9 days prior to being handled daily for an additional 5 days prior to behavioral testing as a 14-day period has been demonstrated to be needed to see exercise-induced changes in the forebrain cholinergic system (see Hall and Savage, 2016 ). Spontaneous alternation testing procedures, in conjunction with microdialysis collection of hippocampal ACh efflux, was conducted with procedures published in our previous work (see Anzalone et al, 2010 ; Hall and Savage, 2016 ; Fernandez and Savage, 2017 ). Spontaneous alternation is a spatial task that is sensitive to the cholinergic system as well as the functioning of the hippocampus and basal forebrain (for review, see Lalonde, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we developed a brightfield co-labeling stain to assess the Nestin/ChAT populations of neurons as well as the overlap in the Nestin and ChAT neuronal populations. Six sections from every subject (sampling every 5th section) spanning the MS/DB were treated with a standardized ICC protocol (see Roland and Savage, 2009 ; Hall and Savage, 2016 ; Fernandez and Savage, 2017 ). Following rinsing (PB), quench and blocking steps, sections were first processed with the ChAT primary antibody (1:200, goat polyclonal anti-ChAT, cat# AB144P; Millipore, Billerica, MA, United States), and where then incubated in a secondary antibody (biotinylated anti-goat IgG 1:100, cat# BA-5000; Vector Laboratories, Burlingame, CA, United States).…”
Section: Methodsmentioning
confidence: 99%